Complex structural dynamics at adsorbed alkanethiol layers at Au (111) single-crystal domains - Terán Arce, Fernando (1998)
The structure and dynamics of dodecanethiol and butanethiol monolayers adsorbed on Au(111) at 298 K have been followed by in situ and ex situ scanning tunneling microscopy (STM). Results show that a gaslike initial adsorption stage where monatomic deep pit clustering occurs is followed by an advanced adsorption stage in which adlayer structural changes p(n×1) ⇒ (√3×√3)R30° ⇔ c(4×2) take place. The first change is interpreted as the motion of adsorbed molecules from fcc to hcp sites, and the second one is explained by the fluctuations of adsorbed molecules from hollow to bridge sites. The structural fluctuations at adsorbate domains occur simultaneously with fluctuations in the size of monatomic deep pits. These processes reveal the complexity of surface dynamics of alkanethiol adlayers on Au(111) at 298 K.